RECOGNITION FOR THE DIFFERENCE IN MIKE TOLLIN'S RADIO MOVIE (2003): A SOCIOLOGICAL APPROACH - ARIMURTI, DHINAR AGUSTINA (2011)
This study aimed to show the recognition for the difference in Mike Tollin's Radio movie in a Sociological Approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociological approach. The major problem of this study is to reveal how the recognition for the difference influences the major character's in the society in mike Tollin's Radio movie. The objective of this study is to analyze the main character based on sociological approach. In this analyzing Radio, the writer uses qualitative method and sociological approach. The object of the study is Radio movie published in 2003 by Mike Tollin. The data sources are primary data and secondary data sources. The primary data source is the Radio movie itself and the secondary data are the other sources related to the analysis such as the author's biography, book of literary theory, sociological book and article from internet. The method of data collection is library research by collecting and recording both of primary and the secondary data. The technique of data analysis used in this study is descriptive analysis. The outcomes of the study are as follows. Firstly, based on the structural analysis, the director conveys messages that everybody has his own strengths and weaknesses. In order to deliver the message the director creates such character like Cuba Gooding who is the person that has a limited mental and looks like a stupid boy with the radio that always in his hand and he has stammer speech. Secondly, based on the sociological analysis, the movie is closely related to the phenomena in America society in early 21 century. The movie focuses on the society in the American people that have differences with other people but there are many people that do not care about it. So the person strives for recognition can be received by the society becoming good person and being able to receive in the society